Ionic mass transfer at horizontals disc electrodes under longitudinal vibration - Podestá, José J. (1974)
A dimensionless correlation for ionic mass transfer at horizontal discelectrodes under longitudinal vibration has been obtained. Within a certain range of amplitude and frequency the flow is confined to a cylinder adjacent to the electrode. The fluid boundary layer thickness is rapidly reduced when either the frequency or the amplitude is increased. The longitudinal vibration, under controlled potential conditions, produces an ac component in the total current. A comparison of the mass transfer rate equation with others corresponding to different flow regimes reveals that a critical flow rate exists, above which vibration is more efficient than conventional agitation in increasing the mass transfer rate.